Instagram: a waste of time or a source of useful information? - Ivova, N. (ТДАТУ, 2018)
Each of us should spend less time on the Internet, but get more value from there. In our research we will answer the main questions: «Instagram: a waste of time or a source of useful information?» And share interesting accounts that I follow and read with pleasure.
Keywords: Instagram; Internet; time management; psychologists